Investigation into the Constituents of the Seed Oils of Tomato (Lycopersicon Esculentum). Okra (Albelmoschus Esculentus) and Nutmeg (Monodora Myristica) and Their Biological Activities (International Journal of Scientific Research in Science and Technology, 2025)
Volatile oils and fixed oils of the dry seeds of Tomato, Okra and Nutmeg plants found or grown in Katsina, Nigeria were obtained by maceration using n-Hexane. GC/MS analysis was performed using a Shimadzu QP2010 plus series gas chromatography coupled with Shimadzu QP2010 mass spectroscopy detector. Characterization of constituents was done by comparison with the MS library (NIST) and further confirmed by interpreting the observed fragmentation pattern. Comparison of the mass spectra with the database on MS library was done. The antimicrobial screening of the oils was also performed for oils from the seeds of these plants species, Ciprofloxacin and Fluconazole were used as control drugs. The most common major constituents of the fixed oils and their percentages were determined so also the essential oils components The minimum inhibition concentrations and minimum bactericidal/fungicidal activities were evaluated for all the samples. Recommendations for further research was also proffered. The study was expected completed within a period of six months, from April to October. This work was published in an international journal of scientific research The sum of two million two hundred and fifty thousand (2,250 000) has been the expected budget for the work.